Analisis Kemampuan Representasi Matematis Siswa dalam Menyelesaikan Soal Matematika Materi SPLDV - Feri Virnando; Nurhanurawati; Agung Putra Wijaya (FKIP Universitas Mataram, 2026)
This study aims to analyze how junior high school students express their ideas when solving problems related to the System of Linear Equations in Two Variables (SPLDV). Mathematical Representation Ability is essentially a